Wine price determinants: Is there a homogeneous international standard? - Tânia Gonçalves; Jo\~ao Rebelo; Lina Lourenço-Gomes; José Caldas (Wine Economics and Policy, 2021)
This article presents an international comparison of the main determinants of wine prices in specialist online wine shops. Hedonic price functions were estimated for 9624 wines spread among four datasets from France, Italy, Germany and Australia. To explain price variation data was collected on wine classification, closure type, wine origin, medals or awards, vintage, alcohol content, color, and grape variety. Results from quantile regression models show that the wine vintage is a common price driver in all markets and quantiles. A quite similar effect was found for alcohol content. In terms of color, the implicit prices for red and white wines are also structurally different between countries, particularly in origin, blend, closure, awards and age. Thus, the markets should be assumed as heterogeneous, and the extrapolation of the results from one market to another may lead to erroneous management decisions.
Keywords: 330; Country-Based Comparison; hedonic analysis; pricing; quantile regression models; specialist retailer prices